FISH AND FISHERIES OF LAKE JAISAMAND, RAJASTHAN - Rao, P Sambasiva; Durve, V S (Indian Journal of Fisheries, 2011)
The fishery of Lake Jaisamand is supported by major carps, catfishes and murrels. The catfishcontribution to the total catch was invariably high. Amongst major carps Labeo rohita formed a dominantportion. Highest landings of Mystes seengha/a was the feature of catfish catches. Channa maru/iusshared highest catch among murrels. The average fish production from the lake for the last fourteen yearswas 52.27 kg/ha despite indescriminate fishing. There are six tribal fishermen co-operative societiesunder the Rajasthan Tribal Area Development Co-operative Federation. Fish catch has been indicatingdecline during the last four years. Considering the fish catch and primary productivity in terms of carbon,at least three fold increase in the present production appears possible by adopting fishery managementmeasures such as clearance of submerged obstructions, construction of a better and improved fish seedfarm at the dam site, eradication of predators, restricting mesh size and strict enforcement of closed seasonfrom 15 June to 30 September. The possibilities of stocking different varieties of fishes have also beendiscussed.